Weighted cooperative spectrum sensing algorithm based on dempster-shafer evidence theory - Ya-jian ZHOU; Kai LIU; Lin XIAO (Tongxin xuebao)
A weighted cooperative spectrum sensing algorithm based on D-S evidence theory (DS-WCSS) was proposed.The algorithm took energy detector to perform local spectrum sensing,evaluated the credibility difference of cognit ve users according to the means and variances of test statistic in both hypotheses,set credibility weights based on the evaluation of credibility difference,and finally used D-S evidence theory to fuse data and made a decision.Simulation results show that the proposed algorithm has better performance than cooperative spectrum sensing algorithm based on D-S evidence theory and traditional hard-decisions.